الحق في العدول عن العقود المبرمة عن بعد كإحدى الآليات القانونية لحماية رضا المستهلك - الهادي، كزيز; لمين، مسعودي محمد Lamin, Massoudi Mohammed (جامعة عمار ثليجي الأغواط - كلية الحقوق والعلوم السياسية, 2023)
يتأثر في أحيان كثيرة المستهلك بأساليب التسويق الإلكتروني، فيقبل على اقتناء سلعة أو خدمة دون معاينة وبعد تمام العقد يكتشف أن رضاه أنتزع منه وأنه ضحية إغراء وسوء تقدير، وأن تصرفه هذا لا يعبر عن رغبته الحقيقية وإرادته الفعلية، وما أقدم عليه يعتبر في نظر نظرية عيوب الإرادة تصرفا حرا صحيحا خالي من العيوب، من هذه المبررات وأخرى بدت الحاجة الملحة لحماية المستهلك المتعاقد عن بعد، فتدخل المشرع واهتدى إلى منحه مدة معينة للتفكير والتروي، ليقرر خلالها تنفيذ العقد الذي سبق إبرامه أو العدول عنه. ليتناول هذا البحث ويسلط الضوء على موضوع الحق في العدول كإحدى الآليات القانونية لحماية رضا المستهلك، بتحديد مفهومه، وبما أنه يخالف مبدأ القوة الملزمة للعقد، كان علينا البحث على المبررات المقنعة التي جعلت المشرع يمنح هذا الحق للمستهلك، ولإيجاد طبيعته وأساسه القانوني الذي يقوم عليه، لا بد من تمييزه عن بعض الأنظمة المشابه له، وخلص البحث إلى توضيح نطاق ممارسة الحق في العدول عن العقود المبرمة عن بعد ومعرفة أثاره القانونية. It may happen that the consumer is affected by the methods of electronic marketing, so he accepts the acquisition of a good or service without finding, and after the execution of the contract he discovers that his satisfaction has been taken away from him, and that he is a victim of temptation and miscalculation and that his behavior does not express his true desire and real will, and what he has done is considered according to the management fault theory as a free and correct behavior free from defects, of these and other justifications, the imperious need to protect the consumer contracting at a distance appeared the legislator then intervened and was guided to grant him a certain period of reflection and deliberation, during which he decided to proceed with the execution of the contract previously concluded or to waive it. Thus, this research aims to shed light on the question of the right of withdrawal and waiver; as one of the legal mechanism for the protection of consumer satisfaction by defining its concept and since it violates the principle of binding force of the contract, it was necessary to seek the convincing justifications which pushed the legislator to grant this right to the consumer and to find its nature and the legal basis on which it is based, it is necessary distinguish it from some similar systems The research concluded by clarifying the exercise of the right to terminate contracts concluded at a distance and knowing its legal effects.
Keywords: حق العدول -- العقود الإلكترونية -- الالتزامات التعاقدية -- رضا المستهلك